2007
DOI: 10.1523/jneurosci.0802-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Downregulation of L-type Calcium Currents to Delayed Neuronal Death in Rat Hippocampus after Global Cerebral Ischemia and Reperfusion

Abstract: Transient forebrain ischemia induces delayed, selective neuronal death in the CA1 region of the hippocampus. The underlying molecular mechanisms are as yet unclear, but it is known that activation of L-type Ca 2ϩ channels specifically increases the expression of a group of genes required for neuronal survival. Accordingly, we examined temporal changes in L-type calcium-channel activity in CA1 and CA3 pyramidal neurons of rat hippocampus after transient forebrain ischemia by patch-clamp techniques. In vulnerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 53 publications
4
55
0
Order By: Relevance
“…This observed pattern of reduced surface calcium channel expression is similar to other disease states such as atrial fibrillation [72], colonic inflammation [73] and cerebral ischemia [74]. Although the physiological consequence of this under-expression in AML cells is not known, reduced calcium channel expression was associated with delayed neuronal death following tissue hypoxia [74]. It is therefore possible that AML cells under-express extracellular calcium channels to increase survival, as this would prevent increases in cytosolic calcium that would otherwise result in activation of apoptotic cell death.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This observed pattern of reduced surface calcium channel expression is similar to other disease states such as atrial fibrillation [72], colonic inflammation [73] and cerebral ischemia [74]. Although the physiological consequence of this under-expression in AML cells is not known, reduced calcium channel expression was associated with delayed neuronal death following tissue hypoxia [74]. It is therefore possible that AML cells under-express extracellular calcium channels to increase survival, as this would prevent increases in cytosolic calcium that would otherwise result in activation of apoptotic cell death.…”
Section: Discussionsupporting
confidence: 71%
“…First, interrogation of publically available AML gene expression databases indicated that surface receptors regulating cytosolic calcium levels are significantly under-expressed in AML cells compared to normal cells. This observed pattern of reduced surface calcium channel expression is similar to other disease states such as atrial fibrillation [72], colonic inflammation [73] and cerebral ischemia [74]. Although the physiological consequence of this under-expression in AML cells is not known, reduced calcium channel expression was associated with delayed neuronal death following tissue hypoxia [74].…”
Section: Discussionsupporting
confidence: 60%
“…Although this influx of Ca 2+ represents only a transient and small fraction of the total that accumulates in the cytoplasm during TMT exposure, it could nonetheless be involved in activating intracellular pathways leading to the TMT-induced cell death observed in both in vitro and in vivo systems. In fact, Ca 2+ signalling through voltage-gated Ca 2+ channels, including the L-type has been shown to play a crucial role in regulating cell fate (Nicotera and Orrenius 1998;Tao et al 1998;Berridge et al 2000;Dolmetsch et al 2001;West et al 2001;Toescu et al 2004;Webster et al 2006;Li et al 2007). Cultured rat cortical neurons have been shown to be more resistant than cultured rat hippocampal neurons to TMTinduced apoptosis (Thompson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Provided that oxidative stress is very common in many retinal degenerations, the constitutively increased activity of MAPK-ERK -EGR1 network may represent potential mechanism of increased vulnerability of LRGCs to stress. In parallel to this mechanism, relatively decreased activity of calcium transport system in LRGC can selectively affect survival of this sub-population during calcium overload typically observed in stress (Nakamura et al 1999;Li et al 2007). Although we detected relatively subtle differences in transcriptome activity between the two subgroups of RGCs, it is conceivable that greater differences and contrast responses will be revealed upon exposure of the retina to stress.…”
Section: Discussionmentioning
confidence: 99%